A review on mesenchymal stem cells and their secretome in hepatocellular carcinogenesis and its related signaling pathways: recent update - Jayenth Jayachandran; A. T. Rithi; Abhijit Mitra; Arunkumar Radhakrishnan; Antara Banerjee; Asim K. Duttaroy (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC) is a significant global health challenge, being one of the leading causes of cancer-related mortality. This review focuses on the intricate interactions within the tumor microenvironment and mesenchymal stem cells (MSCs) and it’s secretome in HCC and possible therapeutic responses. MSCs, characterized by their multipotent differentiation and self-renewal capabilities, can influence tumor behavior maybe through its secreted factors, including cytokines, growth factors and extracellular vesicles. This review summarizes the recent findings on role of MSCs in HCC, highlighting its involvement in different cell signaling pathways, including NF-κB, Wnt/β-catenin, Notch1, Stat3, and TGF-β, which play a significant role in HCC and possibly exhibit both tumor-suppressive and/or tumor-promoting effects depending on the activation or deactivation of signaling pathways. Publications related to the topic between 2016 to 2025 were searched using databases like PubMed, Scopus, Google Scholar with keywords viz. HCC, mesenchymal stem cells, secretome, tumor microenvironment, and signaling pathways. Findings from different research studies depict that MSCs and their secretome can exert anti-tumor effects by inducing apoptosis and enhancing immune responses, they may also promote alternate effects like tumor proliferation and metastasis under certain conditions, related to the activation or deactivation of different signalling pathways. This review aims to provide a comprehensive understanding of the multifaceted roles of MSCs in HCC. The dual role and the complexities of MSCs is context dependent. However, advancements in MSC research showed that the modifications of MSCs and secretome-based therapies and targeting the signaling pathways may have the potential to overcome challenges like drug resistance in HCC treatment.